The ROSwell Device - Monfeli, Matt (Proceedings of the Wisconsin Space Conference, 2018)
Plants grown on orbit seem to be experiencing oxidative stress. The gene expression response of the plants to this oxidative stress bears striking resemblance to their response towards dilute hydrogen peroxide (H2O2). Thus, one route towards developing plants better suited to the stresses of spaceflight begins with developing a way to reliably and consistently treat plants with hydrogen peroxide in a laboratory setting. The ROSwell Device embraces this challenge, using 3D-printed components, Arduino and Raspberry Pi microcontroller units, and a solenoid valve mounted on a frame of 80/20 aluminum. The final goal for this device is to construct a reliable method for testing and development of plants designed to grow in space, before sending them into orbit.